Using technology based student led discussions to promote constructive learning in Chinese primary schools - Bao, Wenwen (2017)
The many valuable aspects of Chinese education have been seen throughout the world. For example Chinese teachers have been invited into the UK to instruct UK teachers on how to improve the quality of Mathematics education there. However, from 2001 onwards the government of China has sought to import pedagogies from the West in order to tackle observed problems with their own education system. Many scholars feel the problems the government were trying to address – the lack of critical thinking, a tendency to rote learning and an exam focused mind-set – would lead to failure for these techniques. However, these studies have all been with older students in high school and beyond. Little or no work has focused on students in the primary grades. Casual observation of Chinese primary school students would imply that they have no trouble in coming up with ideas and discussing them. The initiative for the study in this thesis has therefore been to see if this age range of students would be open to discussion based classes. A study was undertaken to determine if the removal of the teacher from control of the discussion would facilitate this age group to partake in face to face discussion. Other aims were to see whether constructivist learning would result or would the face based, hierarchical Confucian background education system prevent this. The original study was encouraging and as a result a technology based intervention was developed to see if this could help to improve the discussion and would allow further opportunities for students to feel able to engage. To encourage this the new system was also made anonymous. A third study was introduced to see if this approach could prove beneficial to the teachers also as to get such approaches adopted in Chinese schools the teachers would also need to see the benefit of the approach.